ANALISIS BRANDING KAFE CILOR MANTUL DALAM MENGOMUNIKASIKAN PRODUKNYA - Aryanti, Silpa; Bintang, Gilang (UKRI, 2025)
This study analyzes the branding of Café Cilor Mantul in communicating its products amidst the competition of culinary MSMEs in Bunijaya Village. The success of Café Cilor Mantul in surviving and growing is the main reason, highlighting the importance of branding for business sustainability. The purpose of this study is to understand how Café Cilor Mantul's branding elements including the logo, brand name, Instagram visuals, and taglineare represented and communicated. The method of this research is descriptive qualitative with a constructivist paradigm, where data is collected through in-depth interviews with the owner and consumers and direct observation of the implemented branding elements. Branding theory is used as the basis for the analysis. The results of this study indicate that Café Cilor Mantul's logo successfully represents its main product through the use of specific icons, attractive colors, and clear typography, in accordance with the owner's objectives. The brand name